The implementation of grocery items identification system using RFID (GIIS) / Noor Azlina Binti Md Norani - Md Norani, Noor Azlina (Faculty of Information Technology and Quantitative Sciences, 2007)
There is a slightly increased on the number of people become blind or visually impaired reported with difficulty in reading or unable to read letters in regular print. Basic activities such as riding a bus or buying a packet of sugar at the grocery store are just some of the challenges for the blind people to face everyday. A common problem for the blind people when go for shopping is to differentiate between containers that feel the same but contain different contents. Besides, blind person must wait a grocery store employee to assist them identify the right product. This will lead to decrease their independence in daily activities. The GIIS project is developed to assist the blind people for identify grocery items during shopping using RFID technology and text to speech system. Within this system, the blind will know the related information of the item which they hold by stamping RFID tag on the RFID antenna before the system convert output text into speech on the hand phone via Bluetooth connection.